High trophic similarity between non-native common carp and gibel carp in Turkish freshwaters: Implications for management - Sadi Aksu; Özgür Emiroğlu; Paride Balzani; J. Robert Britton; Esengül Köse; Irmak Kurtul; Sercan Başkurt; Oğuzcan Mol; Emre Çınar; Phillip J. Haubrock; Pinar Oztopcu-Vatan; Ali Serhan Tarkan (Aquaculture and Fisheries)
Although the detrimental ecological and economic effects of introducing freshwater fish species have been extensively documented, non-native freshwater fishes continue to be introduced in large numbers globally to enhance fisheries and aquaculture. In Turkey, stocking of common carp Cyprinus carpio is practised to provide food security for people and job security for artisanal fishers, resulting in a country-wide distribution. These stockings, however, increase the risk of accidental introductions and have led to introductions and subsequent invasions of gibel carp Carassius gibelio, a globally invasive and highly detrimental fish species. Here, we assessed the growth types, body conditions and trophic interactions via bulk carbon and nitrogen stable isotope analysis of common and gibel carp in both natural and artificial water bodies in Turkey. The results indicated that common and gibel carp express similar growth types and body conditions in all waters and have similar trophic ecologies. This leads to substantial trophic niche overlaps in waters where they co-occur, with the potential for strong interspecific competition. Considering the ongoing stocking of common carp for fishery enhancement, we recommend to specifically target these stockings in waters where gibel carp has already become invasive. Our findings, indeed, suggest that common carp releases have the potential to hamper invasive gibel carp populations by increasing the competitive interactions between the two species.